Lighting up the villages: Livelihood impacts of decentralized stand-alone solar photovoltaic electrification in rural northern Ghana - Naah, John-Baptist S. N.; Hamhaber, Johannes (JNRD - Journal of Natural Resources and Development, 2015)
The dynamics of solar photovoltaic (PV) technology dissemination and utilization has taken center stage in recent years on a global scale, aiming to partly address prevailing rampant energy poverty situations particularly in developing countries. This paper evaluates a flagship electrification project called Ghana Energy Development and Access Project (GEDAP). We purposively sampled 250 solar users in 65 villages across 6 districts in the Upper West region which has the country’s lowest level of electricity access and possibly the highest proportion of abject poverty among its inhabitants compared to the rest of the country. Based on the survey, it can be said that the overall impact assessment of the GEDAP-sponsored off-grid solar PV systems on the quality of life of the local beneficiaries was found to be positively marginal. Among all livelihood assets considered, social capital was markedly enhanced by the provision of modern energy services via isolated solar PV systems. Bottlenecks were identified, including limited system wattage capacity, slight dysfunction of some balance of components, higher interest rates, low technical know-how and inadequate monitoring, all of which are negatively affecting the sustainability of the project. Our findings also indicate that satisfaction derived from solar PV electricity supply among local solar customers differed for varied reasons as follows: moderately satisfied (43%), satisfied (52%), and dissatisfied (5%). For a decisive enhancement of rural livelihoods, we strongly recommend up-scaling system wattage capacity and coverage to build up new or improve upon existing livelihood assets through diversification of the income sources of the local inhabitants.